2016
DOI: 10.1021/acsnano.6b04268
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain-Barrier-Penetrating Albumin Nanoparticles for Biomimetic Drug Delivery via Albumin-Binding Protein Pathways for Antiglioma Therapy

Abstract: Nutrient transporters have been explored for biomimetic delivery targeting the brain. The albumin-binding proteins (e.g., SPARC and gp60) are overexpressed in many tumors for transport of albumin as an amino acid and an energy source for fast-growing cancer cells. However, their application in brain delivery has rarely been investigated. In this work, SPARC and gp60 overexpression was found on glioma and tumor vessel endothelium; therefore, such pathways were explored for use in brain-targeting biomimetic deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
375
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 418 publications
(403 citation statements)
references
References 38 publications
7
375
0
2
Order By: Relevance
“…Furthermore, BMP‐2 can easily be deactivated by enzymes and other physical/chemical reactions . A recent study demonstrated the advantages of serum albumin (human and bovine) nanoparticles as drug carriers, such as biocompatibility and biodegradability . Zhao et al prepared paclitaxel‐loaded bovine serum albumin nanoparticles via a desolvation procedure and achieved the drug entrapment and loading efficiency of 95.3% and 27.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BMP‐2 can easily be deactivated by enzymes and other physical/chemical reactions . A recent study demonstrated the advantages of serum albumin (human and bovine) nanoparticles as drug carriers, such as biocompatibility and biodegradability . Zhao et al prepared paclitaxel‐loaded bovine serum albumin nanoparticles via a desolvation procedure and achieved the drug entrapment and loading efficiency of 95.3% and 27.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also demonstrated that SPARC facilitated glioma cell invasion, and promoted glioma progression by mediating cell survival through AKT activation . We previously reported that SPARC was overexpressed in U87 orthotopic glioma tissues, and interestingly, SPARC expression decreased after treatment with brain‐targeting nanoparticles (NPs) co‐encapsulating paclitaxel (PTX) and fenretinide (4‐HPR), which suggested its function as a therapeutic indicator.…”
Section: Functions Of Abp and Its Roles In Cancer Progressionmentioning
confidence: 99%
“…It was demonstrated that a high level of caveolin‐1 correlated with enhanced Abraxane sensitivity, and caveolin‐1 could serve as a predictive biomarker for the response to albumin‐based chemotherapy . Our previous study showed that gp60 was abundantly expressed in the tumor, and thus, gp60 was a potential target to achieve albumin‐mediated biomimetic delivery in tumors …”
Section: Functions Of Abp and Its Roles In Cancer Progressionmentioning
confidence: 99%
See 2 more Smart Citations